2017
DOI: 10.3389/fonc.2017.00279
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes after Salvage Stereotactic Radiosurgery (SRS) following In-Field Failure of Initial SRS for Brain Metastases

Abstract: PurposeThe optimal treatment strategy following local recurrence after stereotactic radiosurgery (SRS) remains unclear. While upfront SRS has been extensively studied, few reports focus on outcomes after retreatment. Here, we report the results following a second course of SRS for local recurrence of brain metastases previously treated with SRS.MethodsUsing institutional database, patients who received salvage SRS (SRS2) following in-field failure of initial SRS (SRS1) for brain metastases were identified. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
0
35
1
4
Order By: Relevance
“…Although a dose-response-relationship is known for SRS of brain metastases [ 48 ], these data are not mature enough to suggest a specific minimum inhomogeneity for re-SRS, which however may be needed, if the local recurrent metastasis is in fact deemed radio-resistant by definition of failure of initial SRS. On the other hand, some authors [ 42 , 43 ] found a significant correlation of prescribed dose or prescription isodose with radio-necrosis, so that further dose escalation (compared to the initial SRS) should be practiced very carefully, although such a relationship could not be identified in the present data. Data about a direct correlation of mean or maximum biologically effective dose (BED) and outcome, especially in the reirradiation setting are rare, however some authors could show a general correlation of higher doses and better local control after primary, first-line, SRS for brain metastases [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although a dose-response-relationship is known for SRS of brain metastases [ 48 ], these data are not mature enough to suggest a specific minimum inhomogeneity for re-SRS, which however may be needed, if the local recurrent metastasis is in fact deemed radio-resistant by definition of failure of initial SRS. On the other hand, some authors [ 42 , 43 ] found a significant correlation of prescribed dose or prescription isodose with radio-necrosis, so that further dose escalation (compared to the initial SRS) should be practiced very carefully, although such a relationship could not be identified in the present data. Data about a direct correlation of mean or maximum biologically effective dose (BED) and outcome, especially in the reirradiation setting are rare, however some authors could show a general correlation of higher doses and better local control after primary, first-line, SRS for brain metastases [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 66%
“…Importantly, the local control rate was significantly higher for breast cancer histology and the Karnofsky performance status significantly affected the survival rate. In the only other published gantry-based linear accelerator series of re-SRS, Rana et al re-treated 28 patients, 59% of them with single-fraction regimen and achieved 1-year OS of 90.6% and 1-year-LCR of 88.3% [ 42 ]. The overall rate of radio-necrosis was 18.8% and occurred only in lesions treated with single-fraction SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies on the one-year outcome of repeated radiosurgery for local progression reported that local control was 61 to 88%, and OS was 37 to 90.6% [25][26][27]. Toxicity was reported as overall necrosis rates 9.2 to 19% after the repeated SRS or SRT [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The fifth eligible study included 11 patients of interest (a total number of 28 patients with 32 metastases, mainly melanoma [39%]) [18]. The median gross tumor volume (GTV) size was 0.5 and 1.4 cc, respectively and the median dose was 24 and 26.5 Gy, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…Most studies failed to provide useful data for the patients treated with three courses. Only one reported all the time intervals between the three series (10 and 11 months) [18]. The others reported only one interval (median: 10, 12, 13, and 19 months).…”
Section: Reviewmentioning
confidence: 99%